TEXTUAL MEANING STRATEGIES IN UX WRITING OF GO-JEK MOBILE APPLICATION - Ulfah, Ayu Pratiwi (SemanTIK : Teknik Informasi, 2022)
This research intends to examine how textual meaning strategies influence the user of Go-Jek mobile application through UX (User Experience) writing. The data of this research was the UX writing of the Go-Jek mobile application in version 4. 10. 3. All the UX writing in its apps would be disparted into clauses. Then, the theories of UX writing and Systemic Functional Linguistics (SFL), especially the Theme System, are applied in this research. This research has shown that Go-Jek’s UX writing used some textual meaning strategies. The three highest percentages of mood classes are declarative, imperative, and WH-interrogatives. Declarative clauses give a lot of brief information to the user. This information builds the purposeful concept of UX writing. Then, imperative clauses show much conciseness of word choices that eases the user in understanding the guideline of its application step by step. Third, WH- interrogatives clauses indicate conversational or interactivity responses, which create an intimacy between Go-Jek and its user. The interactivity can stimulate and encourage the user to try new services and promotions. Besides, their clear statement or command helps the user in minimizing errors. These strategies are fruitful for both usability and professionalism of the Go-Jek application through UX writing.Keywords; UX writing, User Experience, Systemic Functional Linguistics, Textual meaning